Strengthening social responsibility among students in New Uzbekistan through reforms and achievements - Sultanov Ogabek Sultan Ugli (Goodwood Publishing, 2025)
Purpose: This study examines the impact of education reforms under the New Uzbekistan initiative on university students’ social responsibility, particularly emphasizing civic engagement and participation in community-oriented action. The main objective was to evaluate how effectively these reforms translate into socially responsible behavior and how they contribute to shaping students’ civic identity, moral awareness, and long-term commitment to national development. Research Methodology: A qualitative interpretive phenomenological approach was employed to explore how students internalize social responsibility through moral education, career decision making, and cultural values. Data were gathered through in-depth interviews and focus group discussions with students, educators, and parents to capture their perspectives. This method makes it possible to analyze the influence of family upbringing, institutional mentorship, and cultural traditions while also highlighting the interaction between educational reforms, social expectations, and individual decision-making processes. Results: The findings show that youth social responsibility in New Uzbekistan is rooted in knowledge, moral integrity, and ethical values, and is strengthened by family support, school learning, state initiatives, and cultural–religious heritage. Conclusions: Social responsibility enhances personal development, leadership, and societal participation. It also encourages collaboration, innovation, and global competitiveness, while strengthening community welfare. Limitations: The qualitative focus on sociocultural narratives may not represent the diversity of youth across all regions or socioeconomic groups, and interpretive reliance restricts generalizability of the findings. Contribution: This study provides a culturally rooted framework for understanding how education, family, and institutional support collectively shape youth responsibility in the context of national reforms in Uzbekistan.